BUKIT SIGUNTANG: PERANANNYA DALAM AGAMA BUDDHA PADA MASA KERAJAAN SRIWIJAYA - Retno Purwanti Nadeak (Balai Arkeologi Bali, 2016)
Siguntang hill is one of the sites from Sriwijaya Kingdom period located in Palembang. Based on the findings of artifacts since the early 20th century, the experts believe that Siguntang hill is a religious site, particularly for Buddhism. Nevertheless, evidence in the form of religious buildings (temple) has not been found. Therefore, the purpose of this study is to prove that this is a religious site which played an important role during the Sriwijaya era. The data were collected through excavation and literature study. Data analysis was performed with the identification of archaeological remains, then associated with form and function. The results of the study are statues, inscriptions, chinese ceramic fragmenst which describe Siguntang Hill is the site of religious or whorship center, a Buddhist pilgrim center and a community center of Sriwijaya. In later times, the Siguntang Hill has a role as a place of origin of Malay kings and place of oath. Bukit Siguntang merupakan salah satu situs masa Kerajaan Sriwijaya di Palembang. Berdasarkan temuan artefak sejak awal abad ke-20, para ahli berkeyakinan bahwa Situs Bukit Siguntang adalah situs keagamaan, khususnya Buddha. Namun demikian, bukti-bukti adanya bangunan keagamaan (candi) sampai saat ini belum ditemukan. Tujuan dari penelitian ini adalah untuk mengetahui peranan Bukit Siguntang pada masa Kerajaan Sriwijaya berdasarkan bukti-bukti yang ditemukan. Data dikumpulkan melalui kegiatan ekskavasi dan kajian pustaka. Analisis data dilakukan dengan identifikasi tinggalan arkeologi, kemudian dikaitkan dengan bentuk dan fungsinya. Hasil penelitian adalah arca, prasast, pecahan keramik Cina yang menggambarkan, bahwa Bukit Siguntang merupakan situs keagamaan atau pusat peribadatan, pusat penziarah agama Buddha dan pusat pertemuan masyarakat pada masa Kerajaan Sriwijaya. Pada masa kemudian,Bukit Siguntang memiliki peran sebagai tempat asal-usul raja-raja di Dunia Melayu dan tempat melakukan sumpah.